PENGARUH LINGKUNGAN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PABRIK 5 PT. SURYA TOTO INDONESIA TBK DIVISI SANITARY UNIT CIKUPA DI TANGERANG-BANTEN - Kamia Ramadhini, - (2022)
Performance problems occur in various industries, both manufacturing and services. Performance research also occurs in industries in Indonesia such as in several service industries such as banking, service, as well as manufacturing fields such as food and beverages, electronics. One of the companies engaged in the sanitary industry is PT. Surya Toto Indonesia Tbk. In order to maintain the company's progress on the company's performance, a good employee performance control is needed that involves every employee of the company. there are several factors to improve employee performance with a conducive work environment and improve employee competence. This research aims to obtain the description of the employee's work environment, how the description of competence. This study uses quantitative methods, how to describe the level of employee performance. The sample used was random sampling as many as 142 employees. The analytical technique used is multiple linear regression analysis with the help of computer software SPSS version 25.0. The results of the study can be known, namely. work environment has an influence of 0.761 on employee performance, competence has an influence of 0.427 on employee performance, the influence of work environment and competence on employee performance is 62.4%. And from the results of hypothesis testing, it can be seen that the work environment and competence affect employee performance. Based on the results of the research, the authors recommend that companies continue to improve the knowledge and skills of employees by providing training so that employees can better master the work given so that companies can optimize company goals.